Recent Publications (Quarterly Journal of Economics, 1954)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 68, Issue 4, November 1954, Pages 652–655, https://doi.org/10.1093/qje/68.4.652 Published: 01 November 1954